Political yelds from cultural fields: agency and ownership in a heritage festival in India - Ohri, Lokesh (Ethnos, 2016)
This paper explores the social dynamics enhancing the political agency of folk culture in India where community rituals and traditional performances increasingly find themselves under festival arc lights. Folk arts in the Himalayan Mountains, earlier understood as dev-kār ya or ‘work of the gods’, formerly contextualised as work and duty, once presented in festivals transform into art and precious heritage. We examine how a young Himalayan state, formed after a violent and protracted people's movement, comes to terms with its new, localised political dynamic in which folk arts, as represented in a festival, become potent tools of protest and political mobilisation. While grand ritual performances may always have been stages for political appropriation and protest, shifts in contexts and discourses in a marginalised landscape, with society desperately seeking a new impetus towards economic progress and national relevance, led to a festival becoming fertile ground for reaping harvests that re-negotiate the conceptions of selfhood, social identity and otherness.
Published online 2015
Gesehen am 07.07.2020